Profil kadar asam urat dan kadar kolestrol pemedek Pura Besakih - Apriyanthi, Desak Putu Risky Vidika; Artini, Ni Putu Rahayu; Laksmita, Ayu Saka; Widayanti, Ni Putu; Iriani, Yulidia; Aryasa, I Wayan Tanjung (Universitas Mataram, 2025)
Pura Besakih located in Karangasem district, Bali is one of the largest Hindu worship sites and is considered a center of spirituality. The ceremony of Ida Bhatara Down Kabeh takes place on the tenth month of the Bali Calendar every year. Universitas Bali Internasional (UNBI) has launched a free medical check-up initiative targeting the religious leaders who lead the ceremonies and visitors to the temple who are Hindu during the ceremony. This activity is a real implementation that the UNBI routinely performs every year through Community Services. UNBI collaboration in Pura Besakih not only provides medical check-up but also builds inter-agency relationships and raises the understanding of how vital community health is. This community service activity is carried out through a collaboration between lecturers and undergraduate students of the Bachelor of Medical Laboratory Technology Study Program. This activity has been implemented on April 19, 2023, with a medical check-up covering cholesterol and uric acid levels. This medical examination uses the Point of Care testing method (POCT). This activity concluded that in uric acid tests, there were 40% above normal levels consisting of 34% males (average uric acid levels 8.5 mg/dL) and 66% females (averaged uric Acid levels 6.7 mg/ dL). In the cholesterol tests, 39% were beyond normal levels, which consisted of 26% male (averaging cholesterol levels 230,1 mg/dL) and 74% female (237.2 mg / dL) cholesterol. Â